Behavioural addiction and associated risk factors among high school students - Zeyrek, Ibrahim; Tabara, Muhammed Fatih; Cakan, Mahmut; Karayagmurlu, Ali (Cambridge Univ Press, 2026)
Objective: Investigating the relationship between behavioural addictions and mental health is essential due to their impact on well-being and the significant barriers they create to achieving lasting recovery. The aim of the study was to examine the prevalence of food addiction, problematic internet use, and internet gaming disorder among 866 high school students (grades 9-12) in Turkey, Bing & ouml;l and their associated with impulsivity, emotional regulation, depression, anxiety, and stress.Methods: The sample was selected using a convenience sampling approach. Data were collected via online questionnaires using validated scales and analysed with SPSS package programme.Results: The prevalence of food addiction was 6.9%, problematic internet use 14.3%, and internet gaming disorder 0.9%. Problematic internet use relatively high prevalence likely reflects adolescents' increased exposure to digital devices. Mental health factors were found to be significantly related to behavioural addictions: depression, anxiety, and stress predicted food addiction; depression and stress predicted problematic internet use, and anxiety was linked to internet gaming disorder.Conclusions: This study contributes to the literature by examining multiple behavioural addictions and their common risk factors simultaneously and provides a comprehensive perspective. It is also one of the rare studies examining food addiction with other behavioural addictions. More research is needed to develop better intervention programmes and policies in the issue.
Keywords: Adolescent; anxiety; behavioural addiction; depression; emotional regulation; impulsivity